Promoting science process skills and learning outcomes through cybergogy approaches with PhET media for Junior High School Students - Maulana Ilham Malik Hidayat; Hasan Subekti (Jurnal Pijar Mipa, 2022)
This study aims to describe the implementation of the cybergogy approach in improving Science Process Skills and learning outcomes. The research design used is One Group Pretest Posttest Design with a quantitative approach. The data collection method used is test and observation. The subjects of this study were 16 students of class VIII-A of Junior High School 2 Papar, Indonesia. Observers in this study were two science teachers and one student majoring in science. The instruments used in this study include learning implementation sheets, Science Process Skills observation sheets, pretest and posttest sheets of cognitive learning outcomes. The data analysis technique used quantitative analysis. Implementing learning through the cybergogy approach is carried out well, and a high learning success rate affects the improvement of science process skills and learning outcomes. The pretest of 80% and posttest of 94,4% showed increased cognitive and affective learning outcomes. The average N-Gain result obtained is 0.7 with high criteria. Science process skills as psychomotor and affective aspects experienced a significant increase. The use of PhET media also increased science process skills and learning outcomes. This study concludes that implementing the cybergogy approach to learning using PhET as a V-Lab media can improve science process skills and student learning outcomes.